Stunting Prevention Movement Through Fortification of Moringa Leaves and Mung Bean Flour in Cookies as PMT (Supplementary Feeding) For Toddlers in Medan Sunggal District - Denny Satria; Aminah Dalimunthe; Hafid Syahputra; Vivi Asfianti; Syukur Berkat Waruwu (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Stunting is a serious problem and is also a major nutritional problem. The problem of stunting has a quite serious impact. It can be short-term related to morbidity and mortality in infants and toddlers, medium-term related to low intellectual and cognitive ability, and long-term related to the quality of human resources and degenerative disease problems in adulthood. The average prevalence of stunting in Indonesia from 2015 to 2017 was 31.4%, far above the WHO limit of 20%. The government with Presidential Decree No. 42/2013 has established a national movement for the first 1000 days of life to improve the nutritional status of toddlers as an effort to handle stunting in Indonesia. Because of the mothers' lack of knowledge about stunting, we were moved to do community service in Medan Sunggal District. Based on this thought, this community service activity is carried out to educate women (community) about the importance of good and correct food processing regarding nutrition/nutrition intake for toddlers by making mothers health cadres in the family in the application of functional food processing from natural ingredients such as moringa leaves and mung beans for stunting prevention in Medan Sunggal District.